THE FOCUS ON ‘RURAL DIGITIZATION’: FROM INDIAN PERSPECTIVE - BABU, KOTAKONDA BALAJI; RAMESH, LANDA (International Journal of Psychosocial Rehabilitation, 2020)
“Digital India” is a flagship program taken prestigiously by the Indian Union government in order to empower and transform India into digital economy and knowledge society. This program will be succeeding not only with the act of digitization of urban areas in the country, but focusing on the rural empowerment with digital synchronization. It is possible but not easy as we discuss. This paper encompasses the methods by which rural empowerment is possible. This article mainly focuses on establishment of internet facilitation in remote rural areas, so that the people living there could be able to grab the incredible advantages with it. Along with the internet facilitation other aspects of rural digitization are discussed in suggestions.